COVID-19 and the Twin Transition: How the Recovery Can Boost Sustainable and Inclusive Growth - Debora Revoltella (Intereconomics, 2020)
Europe has a window of opportunity to embark on a recovery that tilts towards digitalisation and a greener economy, and stands to generate sustainable benefits for its people.
Keywords: 330; Coronavirus; Epidemie; Wirtschaftswachstum; Nachhaltige Entwicklung; EU-Staaten